Memória e corpo : inscrição da subjetividade feminina negra na poesia de Elisa Lucinda - Lourenço, Elaine Morais (2024)
The current dissertation search seeks to highlight of silence and the rupture from stereotypes that surround the black woman's body, trough the poetry of contemporaneous artist Elisa Lucinda. All along the literary historiography that compound the Brazilian canon, we face classics that turn into harden many aspects of the black woman, frequently underestimated, passing the slavery period on the country, making this echoes the hideous heritages of the current days. To guide our studies we search on the female black Brazilian’s thinkers the answers of the current social deformity. The identity of the object, by the way, lay on black woman is captured and reported by the activist of the black Brazilian movement and writer Sueli Carneiro, stimulating reflections that hits a specific line of feminist movement who does not recognize the specificities of the black woman. On this sense, the models of fictions on the studies of the professor Leda Maria Martins, contributes to reveal the colonial think, responsible for the suffering made on black women body since the slavery period. Quoting the professor, the memory of wisdom that constitutes the afro-brazillian culture spreads by countless acts of artistic performance, being something beyond the record recorded by the alphabetic letter. Our investigation, by the way, was made by analysis of the reminiscences that makes present on the writing and poetic performance of Elisa Lucinda, contributing with the actual thesis. Foremost, we saw that the black female literature made in Brazil have a singular role on the praise of voice, body and positioning of the black woman, since that make objective yours emancipation, legitimate by memory trough the inscription of a history that, for a long time, it was maintained exclusively through a Eurocentric bias.